Age-Dependent FOSB/ΔFOSB Response to Acute and Chronic Stress in the Extended Amygdala, Hypothalamic Paraventricular, Habenular, Centrally-Projecting Edinger-Westphal, and Dorsal Raphe Nuclei in Male Rats - Kovács, László Ákos; Füredi, Nóra; Ujvári, Balázs; Golgol, Abolfazl; Gaszner, Balázs (Frontiers in Aging Neuroscience, 2022)
FOS proteins are early-responding gene products that contribute to the formation of activator protein-1. Several acute and chronic stimuli lead to Fos gene expression, accompanied by an increase of nuclear FOS, which appears to decline with aging. FOSB is another marker to detect acute cellular response, while ΔFOSB mirrors long-lasting changes in neuronal activity upon chronic stress. The notion that the occurrence of stress-related mood disorders shows some age dependence suggests that the brain’s stress sensitivity is also a function of age. To study age-dependent stress vulnerability at the immediate-early gene level, we aimed to describe how the course of aging affects the neural responses of FOSB/ΔFOSB in the acute restraint stress (ARS), and chronic variable mild stress (CVMS) in male rats. Fourteen brain areas [central, medial, basolateral (BLA) amygdala; dorsolateral- (BNSTdl), oval- (BNSTov), dorsomedial-, ventral- (BNSTv), and fusiform- (BNSTfu) divisions of the bed nucleus of the stria terminalis; medial and lateral habenula, hypothalamic paraventricular nucleus (PVN), centrally-projecting Edinger-Westphal nucleus, dorsal raphe nucleus, barrel field of somatosensory cortex (S1)] were examined in the course of aging. Eight age groups [1-month-old (M), 1.5 M, 2 M, 3 M, 6 M, 12 M, 18 M, and 24 M] of rats were exposed to a single ARS vs. controls. In addition, rats in six age groups (2, 3, 6, 12, 18, and 24 M) were subjected to CVMS. The FOSB/ΔFOSB immunoreactivity (IR) was a function of age in both controls, ARS- and CVMS-exposed rats. ARS increased the FOSB/ΔFOSB in all nuclei (except in BLA), but only BNSTfu, BNSTv, and PVN reacted throughout the examined lifespan. The CVMS did not increase the FOSB/ΔFOSB in BLA, BNSTov, BNSTdl, and S1. PVN showed a constantly maintained FOSB/ΔFOSB IR during the examined life period. The maximum stress-evoked FOSB/ΔFOSB signal was detected at 2–3 M periods in the ARS- and at 6 M, 18 M in CVMS- model. Corresponding to our previous observations on FOS, the FOSB/ΔFOSB response to stress decreased with age in most of the examined nuclei. Only the PVN exerted a sustained age-independent FOSB/ΔFOSB, which may reflect the long-lasting adaptation response and plasticity of neurons that maintain the hypothalamus-pituitary-adrenal axis response throughout the lifespan.